Dynamics of the Mount Nyiragongo lava lake. Issue 5 (13th May 2014) - Burgi, P.‐Y.; Darrah, T. H.; Tedesco, D.; Eymold, W. K.
Abstract: The permanent and presently rising lava lake at Mount Nyiragongo constitutes a major potential geological hazard to the inhabitants of the Virunga volcanic region in the Democratic Republic of Congo (DRC) and Rwanda. Based on two field campaigns in June 2010 and 2011, we estimate the lava lake level from the southeastern crater rim (~400 m diameter) and lava lake area (~46, 550 m 2 ), which constrains, respectively, the lava lake volume (~9 × 10 6  m 3 ) and volume flow rate needed to keep the magma in a molten state (0.6 to 3.5 m 3  s −1 ). A bidirectional magma flow model, which includes the characterization of the conduit diameter and funnel‐shaped lava lake geometry, is developed to constrain the amount of magma intruded/emplaced within the magmatic chamber and rift‐related structures that extend between Mount Nyiragongo's volcanic center and the city of Goma, DRC, since Mount Nyiragongo's last eruption (17 January 2002). Besides matching field data of the lava lake level covering the period 1977 to 2002, numerical solutions of the model indicate that by 2022, 20 years after the January 2002 eruption, between 300 and 1700 × 10 6  m 3 (0.3 to 1.7 km 3 ) of magma could have intruded/emplaced underneath the edifice, and the lava lake volume could exceed 15 × 10 6  m 3 . Key Points: Long‐term lava lake dynamics are simulated using a bidirectional magma flow model Numerical solutions of intrusive to extrusive volume ratios are provided The conduit diameter and funnel‐shaped lava lake geometry are characterized